COMPREHENSIVE ANALYSIS OF TEACHER EMOTIONAL EXHAUSTION AT KHAZAR DISTRICT HIGH SCHOOL USING THE MASLACH BURNOUT INVENTORY - Mir Jalalli, Narmin (Health and Society, 2024)
Teachers play a crucial role in shaping the lives of the students. They influence their academic development, personal growth, and character formation. However, the proficient health of teachers is the foundation of their significant work in modern academia. Sadly, recent studies have shown increased professional deformations, particularly emotional burnout. Therefore, preventing and correcting burnout syndrome in their professional lives has become increasingly important. This study delves into the intricate dynamics of emotional exhaustion among 53 educators within the Khazar District, employing the Maslach Burnout Inventory as the principal diagnostic tool. The findings serve as a foundation for targeted interventions and policy formulation aimed at mitigating burnout and fostering a conducive work environment conducive to teacher well-being and student success. The quantitative component of the study involves administering the Maslach Burnout Inventory to teachers in order to assess their levels of emotional exhaustion, as well as factors such as depersonalization and reduced personal accomplishment. These data will be analyzed to identify patterns and trends in teacher burnout, as well as correlations with demographic variables such as years of experience and gender.This article highlights the issue of emotional burnout in teachers as a problem of their professional deformation and psychological health.